Knowledge and belief - Schmitt, Frederick F., 1951- (Problems of philosophy (Routledge (Firm)), 1992)
Knowledge, from Plato onwards, has been considered in relation to justified belief. Current debate has centred around the nature of the justification and whether justified belief can be considered an internal or extenal matter. Epistemological internalists argue that the subject must be able to reflect upon a belief to complete the process of justification. The externalists, on the other hand, claim that it is only necessary to consider whether the belief is reliably formed, and argue that the ability to know by reflection is not required for a justified belief. In the historical section o.